Comunicação, consumo e memórias em experiências de parto: efeitos, afetos e narrativas performáticas de parturientes - Pereira, Renata Alcalde (2021)
In recent years, the debate on humanized childbirth has increased, which seeks to adapt the birth process under a less hospital bias, understood by its advocates as more human and welcoming, giving women more autonomy over the process. When interested, pregnant women seek information on the various media platforms, especially in the digital environment, where memories materialized by women who have already gone through the experience of childbirth can be found. In this research, we are interested in reports of parturients presented in blogs (online pages that can be understood as diaries), particularly the blog Relatos de Parto, by the photographer and doula Lela Beltrão - the empirical object of this thesis. Under the interrelationship between communication, consumption and memory, the objective of this study is to understand how the memories materialized in the reports on the blog Relatos de Parto show the construction of the parturient subject in the consumption culture as well as the performatical and theatrical narratives. Our theoretical foundation is centered on the following axes: the study of the context neoliberal (DARDOT; LAVAL, 2016), capitalist (LIPOVETSKY; SERROY, 2015; PEALBART, 2016) and of the consumption cultures (HOFF, 2016; ROCHA, 2005; SLATER, 2002), where the parturient subject is located (DELEUZE; GUATTARI, 1995; GUATARRI; ROLNIK, 1996); the tension that involves the identity construction of an ideal mother-woman (DEL PRIORE, 2013; HALL, 2000, 2006; SCAVONE, 2001; SCOTT, 1995; WOODWARD, 2009) and the correct ways to give birth, adding the discussion about doulas as part of the humanized childbirth ritualization process (DINIZ, 2005; HIRSCH, 2013, 2015; PINTO, 2004; SIMAS, 2016; TORNQUIST, 2004; VAN GENNEP, 1978); the digital social media approach (LEMOS, 2008; LEVY, 1999), blogs in particular, as an advertising space and performance thermometer for this ideal mother-woman (HUYSSEN, 2000; NUNES, 2001, 2017) and, finally, the narratives of the self, the investment of the self and the diary as a memory text (HALBWACHS, 2004; HELLER; PERAZZO, 2016; LIMA, 1986; LOTMAN, 1996). The methodological path had the observation of the Blog Relatos de Parto, since 2018, survey and study of the most significant reports; bibliographic and documentary research (reports in digital media) on the contemporary consumption scenario of humanized childbirth; and the specific analysis of three reports (visual and verbal texts) from the Blog, going through the performance of the parturient mother and the investment of herself from the memories of childbirth experiences. As categories of analysis, we use the concepts of rituals (TORNQUIST, 2004; VAN GENNEP, 1978), theatricality (DEBORD, 2003; FÉRAL, 2008, GOFFMAN, 1985), performance (EHRENBERG, 2010; SCHECHNER, 2003; SIBILIA, 2016), and hero's journey (CAMPBELL, 1989). In the end, we identified common narratives among the three analyzed reports, revealing identity references about motherhood, as well as convergences and divergences about childbirth and the consumption rituals that appear in the process, like the presence of the doula as a resignification of the midwife. Nevertheless, this research contributes to the discussion of the experiences of participation in contemporary times under the articulation of communication, memory, consumption and performance.